MEKANISME GCG DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL TERHADAP KOEFISIEN RESPON LABA - Nurika Restuningdiah (University of Merdeka Malang, 2010)
The purpose of this research was to examine the impact of good corporate governance mechanism tocorporate social responsibility (CSR) disclosure and the impact of CSR disclosure to earning responsecoefficient. The proxy of good corporate governance mechanism were institutional ownership, managerialownership, independency of board commisioner and the size of board commisioner. Regression analysis of35 public companies listed in Indonesia Stock Exchange in year 2009 through a random sampling techniqueindicated that only the size of commisioner board had a positive effect CSR disclosure. This study alsoshowed that there was no significant impact of CSR disclosure to ERC. The implication of this study wasrelevant for the decision maker of public companies to consider the size of board commisioner to supportthe good corporate governance mechanism.